Improving Students’ Writing Ability By Using Genre Based Approach - Harahap, Jamila; Rambe, Sojuangon (Institut Agama Islam Negeri Padangsidimpuan, 2019)
This research is done because some problems in writing, and the objectives of the research is to describe the level of achievement of student in writing ability at SMKS PANCA DHARMA Padangsidimpuan. Researcher conducted by classroom action research (CAR) by using Kemis and Robin design. The researcher conducted two test and two cycles in this research. The participant of this research is one class consists of 26 students from class XI-B. The technique of data collection are test, observation, and interview. Based on the result of the research, researcher found that students’ writing ability was improved. It is supported by the result of the testing in cycle 1 was 65 (34.61%) and cycle 2 was 73.84 (65.38%). It can be concluded that Genre Based Approach